"THE ART OF MUSIC IS A FACTOR OF ART TECHNOLOGY AND CREATIVITY" - Jabborova Onakhon Mannapovna; Saparbayeva Dinorakhan Turgunboy qizi (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article talks about ART technology.